2023
DOI: 10.3390/s23136156
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Upper Body and Lower Limbs Kinematics through an IMU-Based Medical System: A Comparative Study with the Optoelectronic System

Abstract: In recent years, the use of inertial-based systems has been applied to remote rehabilitation, opening new perspectives for outpatient assessment. In this study, we assessed the accuracy and the concurrent validity of the angular measurements provided by an inertial-based device for rehabilitation with respect to the state-of-the-art system for motion tracking. Data were simultaneously collected with the two systems across a set of exercises for trunk and lower limbs, performed by 21 healthy participants. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 58 publications
0
13
2
Order By: Relevance
“…SensAA achieved an RMSE of 2.9° to 8° for walking speeds between 3 and 12 km/h. The results of walking at 3 km/h deviated less than those of most previous studies, which reported RMSE values between 3.2° and 5.9° [ 25 , 26 , 27 , 28 , 33 , 34 , 37 , 41 ]. These studies describe the walking activity during their measurement routine only as walking and do not give an exact speed.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…SensAA achieved an RMSE of 2.9° to 8° for walking speeds between 3 and 12 km/h. The results of walking at 3 km/h deviated less than those of most previous studies, which reported RMSE values between 3.2° and 5.9° [ 25 , 26 , 27 , 28 , 33 , 34 , 37 , 41 ]. These studies describe the walking activity during their measurement routine only as walking and do not give an exact speed.…”
Section: Discussioncontrasting
confidence: 88%
“…Wearable systems based on inertial measurement units (IMUs) have been recently a subject of extensive research [ 12 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. These systems, while not yet delivering the same accuracy as optical systems, can be operated everywhere and not only in a stationary environment equipped with cameras.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly for upper extremity (UE) movement, more quantitative kinematic assessments could be especially useful, as they have been less studied than qualitative, visual, and spatiotemporal metrics [ 17 ]. Advances in inertial measurement unit (IMU) sensors and their associated systems have been shown to provide high-quality quantitative data at a lower cost than other conventional methods, including camera-based motion capture [ 17 , 18 , 19 , 20 , 21 , 22 ]. Prior works have demonstrated the feasibility of using IMU systems to assess the clinic or home activity of the UE.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a small chronic stroke cohort demonstrated the feasibility of using the Xsens IMU system to quantify UE workspace, number of reaches, and joint kinematics at time points over several months [ 23 ]. As biosensors improve in capability, ease of use, portability, and cost, they become increasingly feasible for adoption and integration beyond research labs to therapeutic and clinical use [ 19 , 20 , 21 , 22 , 23 ]. However, data from these IMU systems would be more comparable and useful if also collected during specific, known UE tasks in addition to general activities of daily living.…”
Section: Introductionmentioning
confidence: 99%